Challenges faced by science teachers during the COVID-19 pandemic in public schools in the municipality of Milagres-CE (Research, Society and Development, 2023)
The pandemic of COVID-19 brought many challenges to the educational sector. The managing bodies, opted for the emergency suspension of classes in public and private school units in Brazil. Thus, schools and universities opted for remote teaching. With this, many difficulties became evident, such as, for example, the lack of engagement of many students in remote classes, teachers' lack of skills in combining teaching methodologies with technologies. In this perspective, this paper aims to understand the main challenges faced by science teachers in public schools in the municipality of Milagres - CE during the pandemic period. For the development of this work, a qualitative field research was carried out, seeking information about the difficulties faced by science teachers. It took place in four public schools located in the city of Milagres-CE. The results show that remote teaching through the use of technology has become a possible space for learning and that one of the main difficulties of teachers was related to the lack of competence in the use of digital platforms. It is also noteworthy that teacher training is essential to ally technology with their methodologies as a facilitator for the students. So, it can be inferred that it was only possible to continue the school calendar in educational institutions with the help of technological resources. Therefore, technology cooperates for teaching and student learning, and with this, teachers have adopted the use of technological resources in their current methodology simplifying complex subjects in science teaching.